Leda-1/Pianp is targeted to the basolateral plasma membrane by a distinct intracellular juxtamembrane region and modulates barrier properties and E-Cadherin processing - Evdokimov, Konstantin; Schledzewski, Kai; Winkler, Manuel; Schneider, Stefan W.; Goerdt, Sergij; Géraud, Cyrill (Biochemical and biophysical research communications, 2016)
Leda-1/Pianp is a type-I transmembrane protein which is sorted to the basolateral membrane domain of polarized epithelial cells. Here, we investigated trafficking mechanisms and functions of Leda-1/Pianp in MDCK and MCF-7 cells. Basolateral sorting and posttranslational modifications depended on the intracellular juxtamembrane region. Functionally, Leda-1/Pianp increased the transepithelial electrical resistance generated by a polarized cell sheet. Furthermore, resistance to junctional destabilization by tumor cells was enhanced by Leda-1/Pianp indicating increased stability and tightness of intercellular junctions. While Claudin 1 and 4 expression and activities of small GTPases were not affected, γ-Secretase-mediated cleavage of E-Cadherin was attenuated by Leda-1/Pianp. Regulation of proteolytic processing is thus a molecular mechanism by which Leda-1/Pianp can affect junctional integrity and function.